Comprehensive genomic analysis of five kindreds with multiple childhood leukemias: importance of individual functional analysis for rare ETV6 germline variants - Ai Yamada; Shun Nagasawa; Midori Nakagawa; Sachiyo Kamimura; Nami Inoue; Hiroyoshi Watanabe; Masatoshi Takagi; Yuhki Koga; Dai Keino; Hideki Nakayama; Jun Yoshimura; Koichiro Doi; et al. (Human Cell, 2026)
Germline variants in leukemia predisposition genes are increasingly detected in pediatric patients. Nevertheless, the rare variants identified in diagnostic samples may be misinterpreted without variant-level functional evaluation and cautious clinical interpretation. Whole-exome sequencing was performed on 28 individuals from five kindreds in which at least two children developed acute leukemia. Results identified a rare ETV6 variant, c.604C > G (p.Arg202Gly), in monozygotic twins with ETV6::RUNX1 -positive B-cell precursor acute lymphoblastic leukemia. To support variant interpretation, HeLa-cell populations stably expressing FLAG-tagged wild-type ETV6 and p.Arg202Gly and the known loss-of-function control p.Pro214Leu were established. Subcellular localization was assessed via immunofluorescence microscopy with quantitative scoring. Transcriptional repression was evaluated using luciferase reporter assays driven by ETV6 target promoters ( MMP 3 and PF4 ). p.Arg202Gly predominantly showed nuclear localization comparable to WT, whereas p.Pro214Leu was enriched in the cytoplasm. In the reporter assays, similar to WT, p.Arg202Gly retained repression activity. Meanwhile, p.Pro214Leu failed to repress both reporters. The in-silico prediction of nuclear export sequences suggested an additional export signal in p.Pro214Leu, but not in p.Arg202Gly. Collectively, these findings indicate that p.Arg202Gly behaves as WT-like in the assays performed and do not support a loss-of-function effect. Our study emphasizes the importance of variant-level functional assessment for rare ETV6 variants to inform clinical interpretation and avoid overestimation of pathogenicity.